Mengorbankan Korban di Altar Yurisdiksi: Kritik terhadap Overlapping Regulasi Tindak Pidana Kekerasan Seksual Berbasis Elektronik di Indonesia - Seni Kamalia Rizki Fathullah (International Forum of Researchers and Lecturers, 2026)
Regulatory overlap between the Electronic Information and Transactions Law, the Pornography Law, and the Sexual Violence Crimes Law in the handling of online gender-based violence (KBGO) in Indonesia creates a conflict of norms that results in double victimization. This normative legal study aims to identify the concrete forms of victim sacrifice resulting from overlapping regulations and to critique the inability of conflict-resolution mechanisms to address these conflicts through the principle of lex specialis systematica from a substantive justice perspective. The findings reveal four forms of victim sacrifice: victim criminalization, the length of the judicial process, inconsistencies in court rulings, and the failure to fulfill the right to restitution and the right to be forgotten. This study also concludes that the lex specialis systematis principle is inadequate because its dogmatic approach disregards the interests of victims, requires time and expertise that ordinary victims lack, and is not consistently applied in courts. This study recommends a paradigm shift from a dogmatic approach to a victim-centered approach.